Cardiac Magnetic Resonance Imaging–Based Screening for Cardiac Sarcoidosis in Patients With Atrioventricular Block Requiring Temporary Pacing - Aino‐Maija Vuorinen; Jukka Lehtonen; Sami Pakarinen; Miia Holmström; Sari Kivistö; Touko Kaasalainen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Some myocardial diseases, such as cardiac sarcoidosis, predispose to complete atrioventricular block. The European Society of Cardiology Guidelines on cardiac pacing in 2021 recommend myocardial disease screening in patients with conduction disorder requiring pacemaker with multimodality imaging, including cardiac magnetic resonance (CMR) imaging. The ability of CMR imaging to detect myocardial disease in patients with a temporary pacing wire is not well documented. Methods and Results Our myocardial disease screening protocol is based on using an active fixation pacing lead connected to a reusable extracorporeal pacing generator (temporary permanent pacemaker) as a bridge to a permanent pacemaker. From 2011 to 2019, we identified 17 patients from our CMR database who underwent CMR imaging with a temporary permanent pacemaker for atrioventricular block. We analyzed their clinical presentations, CMR data, and pacemaker therapy. All CMRs were performed without adverse events. Pacing leads induced minor artifacts to the septal myocardial segments. The extent of late gadolinium enhancement in CMR imaging was used to screen patients for the presence of myocardial disease. Patients with evidence of late gadolinium enhancement underwent endomyocardial biopsy. If considered clinically indicated, also 18‐F‐fluorodeoxyglucose positron emission tomography and extracardiac tissue biopsy were performed if sarcoidosis was suspected. Eventually, 8 of 17 patients (47.1%) were diagnosed with histologically confirmed granulomatous inflammatory cardiac disease. Importantly, only 1 had a previously diagnosed extracardiac sarcoidosis at the time of presentation with high‐degree atrioventricular block. Conclusions CMR imaging with temporary permanent pacemaker protocol is an effective and safe early screening tool for myocardial disease in patients presenting with atrioventricular block requiring immediate, continuous pacing for bradycardia.